Host defence peptide (HDP) human beta defensin 9 (HBD9) - Omar, Nazri (2016)
Introduction: The emergence of antibiotic resistance has led to the continuing search for discovery of effective antibiotics. Host defence peptides (HDPs) confer defence mechanisms against infection and investigation of their specific roles and interplays are ongoing. Among the HDPs, defensins are a group of effector molecules which plays important roles in humans. Although several stereotypes of human beta defensins (hBDs) such as the hBD1-3 are well studied, other members including the human beta defensin 9 (hBD9), are not entirely known. Understanding the properties of these HDPs will enable us to discover a safe and efficacious, broad-spectrum and resistance-free antibiotic for therapeutic application in the future.